Profile and complexity of travel medicine consultations in Chile: unicentric cross-sectional study - Thomas Weitzel (BMJ Open)
Objective To analyse the spectrum, vaccination needs and pretravel advice complexity of travellers presenting at a travel medicine clinic in Santiago, Chile.Design Cross-sectional study.Setting Pretravel consultations in a private healthcare centre in Chile, an ‘emerging market’ country in South America.Participants Travellers (n=1341) seeking pretravel advice at the Travel Medicine Program of Clínica Alemana, Santiago, from April 2016 to March 2018.Primary and secondary outcome measures Demographical and travel characteristics, indications for travel vaccines and malaria prophylaxis, and complexity of travel consultations.Results Of 1341 travellers, 51% were female; the median age was 33 years. Most frequent travel reasons were tourism (67%) and business (20%). Median travel duration and time to departure were 21 days and 28 days, respectively. Most destinations were located in America (41%), followed by Asia (36%) and Africa (26%); 96% visited less developed countries, mostly in tropical regions, with risk of arboviral infections (94%) and malaria (69%). The indicated vaccine indications comprised hepatitis A (84%), yellow fever (58%), typhoid fever (51%), rabies (29%), polio (8%), Japanese encephalitis (6%) and meningococcal meningitis (5%). More than 60% of consultations were classified as complex.Conclusion The studied population mostly visited less developed tropical regions, resulting in a high requirement of yellow fever and other travel-related vaccinations. Most consultations were complex and required a comprehensive knowledge and training in travel medicine.